P121 Second-Line Biologic Therapy Persistence in a Multicentre Cohort of Inflammatory Bowel Disease Patients. (21st January 2022) - Doherty, J; Stack, R; O Morain, N; Corcoran, R; Ryan, B; Doherty, G; Mc Namara, D; Kevans, D
Abstract: Background: Anti-TNF agents are effective treatments for Inflammatory Bowel Disease (IBD), however, a significant proportion of patients require second-line biologic therapy. Real-world data on the outcome of second line biologic therapy can inform clinical decision-making. Methods: To evaluate prescribing practice and second-line biologic therapy persistence in IBD patients. IBD patients, who had received one prior anti-TNF agent and commenced a second-line biologic, at participating centres, were identified. Baseline demographic data, concomitant medication and biologic therapy history were characterised by retrospective review of patients records. Adalimumab(ADA) and golimumab(GOL) were considered subcutaneous(SC) anti-TNF agents. Date of commencement and discontinuation of therapies were documented. Kaplan-Meier survival curves were constructed for time based analyses. P values < 0.05 were considered significant in analyses. Results: N=395 IBD patients were included; 30%, 68% and 2% had UC, CD and IBD-U respectively; age (median[IQR]) 26[18–35] years; 56% female; 35% receiving a concomitant immunomodulator (IMM); follow-up time (median [IQR]) 1.5[0.7–3.3] years. Second-line biologic therapy with SC anti-TNF, infliximab(IFX), vedolizumab(VDZ), and ustekinumab(USTK) was used in 36%(n=143), 38%(n=151), 10%(n=38), and 16%(n=63) of patients respectively. Follow-up time (median[IQR]) was significantly longer for SC anti-TNF and IFX compared with VDZ and USTK groups: 1.7 [0.7–3.6], 1.7 [0.7–3.5], 1.1[0.3–2.5], 1.3[0.5–2.3] years respectively, p=0.03. A greater proportion of patients receiving anti-TNF therapy versus alternate class biologic therapy received a concomitant IMM: 42%, 34%, 18% and 29% of SC anti-TNF, IFX, VDZ and USTK treated patients respectively, p=0.03. In a univariate survival analysis there was no significant difference in survival-free of drug discontinuation comparing second-line biologic agents, p=0.8. In a multivariate analysis, including second-line biologic agent type, concomitant IMM use, gender and IBD phenotype the only factor significantly associated with time to drug discontinuation was UC phenotype, Hazard ratio (95%CI): 1.5 (1.1 – 2.1), p=0.007. Conclusion: While follow-up time was shorter for VDZ and USTK treated patients, the durability of response to second-line biologic therapy, assessed by drug persistence, appeared similar between agents. UC phenotype was associated with a shorter time to therapy discontinuation.